Three SNARE complexes cooperate to mediate membrane fusion - Hua, Yuanyuan (The National Academy of Sciences, 2001)
Soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins of the syntaxin, SNAP-25, and VAMP families mediate intracellular membrane fusion through the formation of helical bundles that span opposing membranes. Soluble SNARE domains that lack their integral membrane anchors inhibit membrane fusion by forming nonfunctional complexes with endogenous SNARE proteins. In this study we investigate the dependence of membrane fusion on the concentration of a soluble SNARE coil domain derived from VAMP2. The increase in the inhibition of fusion observed with increasing concentration of inhibitor is best fit to a function that suggests three SNARE complexes cooperate to mediate fusion of a single vesicle. These three complexes likely contribute part of a protein and lipidic fusion pore.